Integrating Game-Based Learning to Address Challenges Experienced by English Teachers at SMP Bina Bangsa - Wulandari, Efri Putri; Safriyani, Rizka; Agustina, Dwi (ICONELT, 2024)
In the context of the Indonesia Merdeka curriculum, this research investigates what challenges English teachers at Bina Bangsa Junior High School face in taking a pedagogical approach to anticipate the needs of diverse students. Every teacher has challenges and this research will address the implementation of adaptive teaching strategies, which may be hindered by limited resources and professional development opportunities. Using a qualitative approach and Collaborative Classroom Action Research (CCAR), this study explores how game-based learning (GBL) can be integrated into English language teaching to address these challenges. Through teacher interviews and classroom observations, this study reveals that understanding students’ diverse backgrounds, language proficiency, and learning preferences promotes an inclusive learning environment. The research also found that GBL effectively increased students’ motivation and participation, especially in grammar comprehension. The research also looks at CCAR as a reflective and collaborative framework that supports teacher development and the implementation of innovative teaching methods. The findings suggest that the combination of GBL and CCAR can improve English language teaching practices, make classrooms more responsive to student diversity, and enhance overall learning.